2012
DOI: 10.1111/j.1532-849x.2011.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Rehabilitation of an Orbital and Facial Defect: A Clinical Report

Abstract: For patients undergoing radical head and neck surgery, the deformity or physical defect adds to the agony. Rehabilitation of patients with such deformities is a challenge for the maxillofacial prosthodontist to enhance the esthetics and give psychological strength to the patient. This clinical report describes the rehabilitation, using a silicone prosthesis, of a large facial and orbital defect due to mucoepidermoid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 13 publications
0
23
0
5
Order By: Relevance
“…Facial prostheses retaining to anatomical and/or surgical undercuts; also retaining with mechanical aids have been still reported [3,[6][7][8][9][10][11]. Hatamleh et al [12] reported that, ocular prostheses included in their study were entirely retained by undercuts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial prostheses retaining to anatomical and/or surgical undercuts; also retaining with mechanical aids have been still reported [3,[6][7][8][9][10][11]. Hatamleh et al [12] reported that, ocular prostheses included in their study were entirely retained by undercuts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, weight reduction by using hollow prosthesis may contribute to the retention [5]. Already existing anatomical structures or undercut areas of the defect are employed to retain the facial prostheses conventionally [6][7][8]. Mechanical retention obtained by eyeglasses, straps or headbands, has been used for a long time [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomy of the defect can be recorded accurately by rapid prototyping rather than conventional impression techniques to restore the facial prosthesis [46]. The advantage of maxillofacial prostheses is that, it requires less or no surgery as it restores the esthetics and function in a near natural appearance [13].…”
Section: Discussion Ocularmentioning
confidence: 99%
“…Impression tray is fabricated from a baseplate wax by warming it over the flame and adapting it around the contours of the eye. The location of the pupil is marked and a perforation with a diameter of 3-4 mm is made on the baseplate wax with many perforations in the surrounding wax [13]. Light body material is placed over the anatomical structure to be recorded and medium body impression material added.…”
Section: Preparation Of the Site Ocularmentioning
confidence: 99%
See 1 more Smart Citation